The Effect of Intentional Weight Loss on Fracture Risk in Persons With Diabetes: Results From the Look AHEAD Randomized Clinical Trial. (28th July 2017) - Johnson, Karen C; Bray, George A; Cheskin, Lawrence J; Clark, Jeanne M; Egan, Caitlin M; Foreyt, John P; Garcia, Katelyn R; Glasser, Stephen; Greenway, Frank L; Gregg, Edward W; Hazuda, Helen P; Hergenroeder, Andrea; et al.
ABSTRACT: Intentional weight loss is an important treatment option for overweight persons with type 2 diabetes mellitus (DM), but the effects on long‐term fracture risk are not known. The purpose of this Look AHEAD analysis was to evaluate whether long‐term intentional weight loss would increase fracture risk in overweight or obese persons with DM. Look AHEAD is a multicenter, randomized clinical trial. Recruitment began in August 2001 and follow‐up continued for a median of 11.3 years at 16 academic centers. A total of 5145 persons aged 45 to 76 years with DM were randomized to either an intensive lifestyle intervention (ILI) with reduced calorie consumption and increased physical activity designed to achieve and maintain ≥7% weight loss or to diabetes support and education intervention (DSE). Incident fractures were ascertained every 6 months by self‐report and confirmed with central adjudication of medical records. The baseline mean age of participants was 59 years, 60% were women, 63% were white, and the mean BMI was 36 kg/m 2 . Weight loss over the intervention period (median 9.6 years) was 6.0% in ILI and 3.5% in DSE. A total of 731 participants had a confirmed incident fracture (358 in DSE versus 373 in ILI). There were no statistically significant differences in incident total or hip fracture rates between the ILI and DSE groups. However, compared to the DSE group, the ILI group had a statistically significant 39% increased risk of a frailty fracture (HR 1.39; 95% CI, 1.02 to 1.89). An intensive lifestyle intervention resulting in long‐term weight loss in overweight/obese adults with DM was not associated with an overall increased risk of incident fracture but may be associated with an increased risk of frailty fracture. When intentional weight loss is planned, consideration of bone preservation and fracture prevention is warranted. © 2017 American Society for Bone and Mineral Research.